The Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Yang Berdampak Pada Kinerja Salesman Pada Honda Kumala Karawang - Widjaja Makmur; Sonny Hernosa; Nunung Nurhasanah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to provide empirical evidence about the effect of compensation, work environment on job satisfaction which has an impact on salesman performance at Honda Kumala Karawang. The population and research sample used were 83 sales people with the sampling technique being the saturated sampling method. The analytical method used is path analysis. The results showed that compensation and work environment partially had a positive and significant effect on salesman job satisfaction at Honda Kumala Karawang, compensation and work environment partially had a positive and significant effect on salesman performance at Honda Kumala Karawang and job satisfaction partially had a positive and significant effect on salesman performance on Honda Kumala Karawang. Simultaneously shows that compensation and work environment on job satisfaction have a positive and significant impact on the performance of Salesman Honda Kumala Karawang. Keywords: compensation, work environment, job satisfaction, performance